Cyclic microwave-assisted synthesis of Cu3BiS3dendrites using L-cysteine as a sulfur source and complexing agent - Kamonwan Aup-Ngoen (2018)
Nanostructured Cu3BiS3dendrites were successfully synthesized from CuCl, BiCl3and L-cysteine in ethylene glycol (EG), using cyclic microwave radiation (CMR). The phase was detected by X-ray diffraction (XRD) and selected area electron diffraction (SAED), and was in accordance with that obtained by the simulation. Scanning and transmission electron microscopic (SEM and TEM) techniques revealed the gradual transformation of nanoparticles to nanostructured dendrites, due to the increase of microwave power. Photoluminescence of Cu3BiS3dendrites was a blue emission centered at 367 nm. © 2010 Elsevier B.V. All rights reserved.